1.
"3x\u00b2 + 2x \u2013 1=0"
Here, we can apply quadratic formula
"x = \\frac{\u2212b\u00b1 \\sqrt{b^2\u22124ac} }{2a}"
Where a = 3, b = 2, c = -1
Plugging these into the equation, we have;
"x = \\frac{\u22122\u00b1 \\sqrt{2^2\u2212(4\u00d73\u00d7-1)} }{2\u00d7-1}"
"x = \\frac{\u22122\u00b1\u221a16}{6}"
"x= \\frac{1}{3}" or "x = -1"
2.
"x^3 - 27 =0" -27 crosses the other side
"\\implies x^3 = 27" take the cube root of both sides
"\\implies \\sqrt[3]{x^3} = \\sqrt[3]{27}"
"x = 3"
3.
"\\mathrm{For\\:a\\:polynomial\\:equation\\:with\\:integer\\:coefficients:\\quad }a_nx^n+a_{n-1}x^{n-1}+\\ldots +a_0"
"\\mathrm{If\\:}a_0\\mathrm{\\:and\\:}a_n\\mathrm{\\:are\\:integers,\\:then\\:if\\:there\\:is\\:a\\:rational\\:solution}"
"it\\:could\\:be\\:found\\:by\\:checking\\:all\\:the\\:numbers\\:produced"
"\\:for\\:\\pm \\frac{dividers\\:of\\:a_0}{dividers\\:of\\:a_n}"
Therefore, given the polynomial x³ +4x² + 5x + 2, we have;
"a_0=2, and\\:\\quad a_n=1"
"\\mathrm{The\\:dividers\\:of\\:}a_0:\\quad 1,\\:2, and\\:\\quad \\mathrm{The\\:dividers\\:of\\:}a_n:\\quad 1"
So, "\\mathrm{The\\:possible\\:zeros\\:numbers\\:are\\:\\:}\\quad \\pm \\frac{1,\\:2}{1}" or "\\quad \\pm \\frac{1}{1}" , "\\quad \\pm \\frac{2}{1}"
And the rational zeros are obtained when these are replaced in the polynomial "x^3+4x^2+5x+2" , we have "x = -1, and , x=-2"
4.
"3x\u00b3 + 11x\u00b2 + 5x \u2013 3"
The above procedure applies to this polynomial where;
"a_0=3, and\\:\\quad a_n=3"
And "\\mathrm{the\\:dividers\\:of\\:}a_0:\\quad 1,\\:3,\\:\\quad \\mathrm{The\\:dividers\\:of\\:}a_n:\\quad 1,\\:3"
Hence the possible zeros are "\\pm \\frac{1,\\:3}{1,\\:3}"
And the rational zeros are, when plugged back into the polynomial
"3x\u00b3 + 11x\u00b2 + 5x \u2013 3" , we have; "x=-1,\\:x=-3,\\:x=\\frac{1}{3}"
Comments
Leave a comment